2011
DOI: 10.1016/s1130-1473(11)70108-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic analysis of hospital acquired infections in patients diagnosed with brain tumor in a tertiary hospital

Abstract: SummaryObjectives. To analyze the relationship between hospital acquired infections and clinical outcomes, duration of stay, and cost per infectious episode in patients diagnosed with brain tumors in our service.Materials and methods. We conducted a retrospective study on patients diagnosed with brain tumors and admitted to the department of neurosurgery in the Cruces Hospital of the University of the Basque Country between January 1st, 2007 and December 31st, 2007. We collected demographics, responsible patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…We found that male was more affected than female and the mean age was 29.9 years-old, it is nearly consistent to the previous study by Ngai Kien Le et al [38]. Nevertheless, other study have reported that female was more affected than male and mean age was higher compared to the current study [39].…”
Section: Discussionsupporting
confidence: 92%
“…We found that male was more affected than female and the mean age was 29.9 years-old, it is nearly consistent to the previous study by Ngai Kien Le et al [38]. Nevertheless, other study have reported that female was more affected than male and mean age was higher compared to the current study [39].…”
Section: Discussionsupporting
confidence: 92%
“…general hospital inpatients [2,3]. Only a limited number have evaluated their impact on cancer patients and these studies were often constrained by speci c types of cancer [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a prospective monitoring case-control study of 448 patients undergoing colorectal cancer surgery in China presented that the total direct economic burden due to HAI was 1,589.30 dollars [5]. While, a retrospective study in Europe on 139 patients diagnosed with brain tumors reported a mean cost 17,097 euros [4] and another previous study in USA on gynecologic tumor estimated the cost 58,000 dollars[6]. Certainly, the economic loss due to HAIs varies in different studies by the region of study, the characteristics of study population, the structure and composition of disease and the types of infection.…”
Section: Burden Of Haismentioning
confidence: 99%
“…In a study of patients with brain tumors admitted to a neurosurgery department, the mean length of hospital stay for all patients was similar to our study (14.34 days). However, the average length of hospital stay for patients with NI was 25 more days than for patients without infections ( p < 0.01) [ 40 ]. Unlike our study, 20% of NI were neurosurgical site infections which are associated with significant morbidity and a longer hospital stay and require complex treatment including long-term antibiotic therapy [ 41 ].…”
Section: Discussionmentioning
confidence: 99%